The Administrative Factors Affecting Lifelong Learning for Military Personnel at the Military Units under the Royal Thai Kingdom Army Policy - Chaiparinya, Somsupang; Pengchan , Teerapol; Homsin, Nawattakorn (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were: 1) To study multi-level factors that affect lifelong learning in military units, 2nd Army Area. 2) To create a multi-level model that affects lifelong learning in military units, 2nd Army Area.The sample group includes commanders, military instructors and regular soldiers, 1st shift, year 2023, 2nd Army Area, totaling 1,138 personnel. They were selected by the method of calculating the sample group of the G*Power program and multi-stage random sampling, the research instrument for the data collection were questionnaire with rating scale on individual level factors organizational factors affecting lifelong learning in military units, 2nd Army Area. The statistics for data analysis include: percentage, mean, standard deviation Pearson's correlation and regression analysis using the linear descending grade level program (HLM 7 Student). The research results were found as follows; (1) Multi-level factors affecting lifelong learning in military units, 2nd Army Area consists of personnel level factors is at a moderate and organizational factors is at a moderate (2) A multi-level model that affects lifelong learning in military units, 2nd Army Area found that (2.1) Personnel level factors include leadership, organizing teaching and learning activities using media and teaching equipment, educational policy, course of study management and organizational atmosphere. It has a positive impact on lifelong learning in the military unit, 2nd Army Area. (2.2) Organizational level factors include organizational climate educational, policy educational, course of study and management. It has a positive impact on lifelong learning in the military unit, 2nd Army Area and coefficient determination (R2) predictive value. The R2 values indicate that 46%, 41%, and 42% of their AM, LLA, and RSMP lifelong learning activities were attributable to their personnel factors, and 68%, 75%, and 71% of their organizational factors towards their MAM, MLLA, and RSMP were significantly (p<.05), respectively.